2012
DOI: 10.1186/1471-2180-12-106
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus grown in peptone as the carbon source exhibits spore density- and peptone concentration-dependent aflatoxin biosynthesis

Abstract: BackgroundAflatoxins (AFs) are highly carcinogenic compounds produced by Aspergillus species in seeds with high lipid and protein contents. It has been known for over 30 years that peptone is not conducive for AF productions, although reasons for this remain unknown.ResultsIn this study, we showed that when Aspergillus flavus was grown in peptone-containing media, higher initial spore densities inhibited AF biosynthesis, but promoted mycelial growth; while in glucose-containing media, more AFs were produced wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…Spore inoculum was prepared as described by Yan et al [23]. Sixty microlitre of A. parasiticus spore suspensions stored at −80 °C in 20 % glycerol was sub-cultured on potato dextrose agar plates at 37 °C for 4 days.…”
Section: Fungal Strain and Preparation Of Spore Inoculummentioning
confidence: 99%
“…Spore inoculum was prepared as described by Yan et al [23]. Sixty microlitre of A. parasiticus spore suspensions stored at −80 °C in 20 % glycerol was sub-cultured on potato dextrose agar plates at 37 °C for 4 days.…”
Section: Fungal Strain and Preparation Of Spore Inoculummentioning
confidence: 99%
“…According to Georgianna and Payne, (2009) the 442 regulation of STERIG and especially aflatoxin production by Aspergillus generally require simple 443 sugars, low pH, reduced nitrogen source and mild oxidative stress. Recent studies have even shown 444 that when A. flavus was grown in peptone-containing media, higher initial spore densities inhibited 445 aflatoxin biosynthesis, but promoted mycelial growth (Yan et al, 2012). However, it is still hard to say 446 that this could be the reason in our substrate for its observed low AFG production, since they still 447 produced high level of B aflatoxins.…”
mentioning
confidence: 96%
“…Peptides can be absorbed into the cell and metabolized into amino acids. Then, by deamination or oxidative deamination, these amino acids are converted into intermediates of tricarboxylic acid cycle such as serine → pyruvate, aspartate → oxaloacetate, glutamate → 2-oxoglutarate [24][25]. However, the catabolic pathways of many amino acids remain unknown or only partially characterized.…”
Section: Composition Of Culture Medium (Concentrated Glycerol From Bimentioning
confidence: 99%
“…However, the catabolic pathways of many amino acids remain unknown or only partially characterized. In this context, arginine and histidine are known to provide energy [24][25]. Yan et al [25] evaluated the aflatoxin production from Aspergillus flavus using a culture medium comprised by salts and peptone as sole carbon source.…”
Section: Composition Of Culture Medium (Concentrated Glycerol From Bimentioning
confidence: 99%
See 1 more Smart Citation